Registry of mass spectral data - Stenhagen, Einar (John Villey and Sons, 1974)
Mass spectrometry is used extensively to identify unkown chemicals in almost all areas of chemistry, biochemistry, medical chemistry, and the environmental sciences. This massive work has been compiled and written by two acknowledged leaders in their field.